“It’s Awfully Important to Listen”: Ella Jenkins and Musical Multiculturalism - Wald, Gayle (Current Musicology, 2019)
The 1995 release of Multicultural Children’s Songs (Smithsonian-Folkways) solidified the reputation of Ella Jenkins (b. 1924) as the most prolific and influential U.S. children’s musician of the late 20th century. Yet while the album brought Jenkins’s music to new audiences, the compilation of her work under the “multicultural” moniker threatened to obscure the radicalism of her repertoire and pedagogical method. Focusing on her 1957 Folkways debut, Call-and-Response Rhythmic Group Singing, I argue that Jenkins models a black feminist approach to early childhood musical education that assails cultural hierarchies, imagines “difference” outside of essentializing representation, and recognizes song as a vehicle of cultural memory and subjugated knowledge, even for very young audiences.